Rapid hippocampal plasticity supports motor sequence learning - Jacobacci, Florencia; Armony, Jorge L; Yeffal, Abraham; Lerner, Gonzalo; Amaro, Jr, Edson; Jovicich, Jorge; Doyon, Julien; Della-Maggiore, Valeria (Proceedings of the National Academy of Sciences - PNAS, 2020)
Recent evidence suggests that gains in performance observed while humans learn a novel motor sequence occur during the quiet rest periods interleaved with practice (micro-offline gains, MOGs). This phenomenon is reminiscent of memory replay observed in the hippocampus during spatial learning in rodents. Whether the hippocampus is also involved in the production of MOGs remains currently unknown. Using a multimodal approach in humans, here we show that activity in the hippocampus and the precuneus increases during the quiet rest periods and predicts the level of MOGs before asymptotic performance is achieved. These functional changes were followed by rapid alterations in brain microstructure in the order of minutes, suggesting that the same network that reactivates during the quiet periods of training undergoes structural plasticity. Our work points to the involvement of the hippocampal system in the reactivation of procedural memories.